Pelatihan Videografi Balai Latihan Kerja Al Ittihad dengan Model Project Based Learning - Soetam Rizky Wicaksono; Didit Prasetyo Nugroho (Journal of Community Development, 2021)
The pandemic outbreak has had an impact on the field of employment in general, so the Al Ittihad BLK (Balai Latihan Kerja or Work Training Centre) is trying to improve the digital skills of the learning participants to be more competitive during and after the pandemic. BLK, whose participants are the majority of alumni from the Al Ittihad Islamic boarding school, is expected to get additional ability to increase competitiveness in the world of work. The Ma Chung University community service team, which had discussed in a brainstorming session with the BLK managers, then agreed to provide videography training with the PBL (Project Based Learning) model with the assumption that the model was better able to increase the enthusiasm for learning and optimize the creative potential of the participants. The training, which was carried out offline for a limited time in the Poncokusumo area, Malang Regency, was proven to be able to improve the skills of the participants in learning and more visible learning outcomes based on the video project made by the participants. So it can be concluded that the implementation of the PBL model in this training process can be more effective in the limited training period.